Pengaruh Penggunaan Dan Keefektifan Aplikasi Srikandi Terhadap Sistem Persuratan Di Organisasi Perangkat Daerah (OPD) Kecamatan Di Kabupaten Nganjuk - Purwati, Linda (Jurnal Ilmiah Matrik, 2024)
Advances in information and communication technology are increasingly developing, the industrial revolution in the government sector has brought changes to the correspondence system. The SRIKANDI application is one of the media for the revolution of letters from paper or physical form to electronic or digital form. In the SRIKANDI application there are menus for creating letters, sending letters, dispositioning, signing, and archiving letters. The aim of this research is to analyze the influence of the use and effectiveness of the SRIKANDI application on the correspondence system in the Subdistrict Regional Apparatus Organization (OPD) in Nganjuk Regency. Using explanatory research and a quantitative approach. Data analysis uses classical assumption tests, multiple linear regression tests, and hypothesis testing. The results of data processing show that there is an influence on the use and effectiveness of the SRIKANDI application on the correspondence system in the Subdistrict Regional Apparatus Organizations (OPD) in Nganjuk Regency, both partially and simultaneously